Pemodelan Matematika Dalam Optimasi Laba Produksi Olahan Opak Singkong di UD Opak Rizky - M. Farhan Zacky; Akhiriyah Ramadhani; Juliani; Juliana (JMT (Jurnal Matematika dan Terapan), 2024)
The goal of this study is to identify the most lucrative mathematical model and solution to maximize cassava opak production at Ibu Hesti's facility. The owners, managers, and workers of the Cassava Opak factory were interviewed for this study, which used descriptive quantitative approaches to examine data. The acquired data is utilized as a reference to develop a mathematical model. The solution to this mathematical model is then found using the simplex approach. Prior to developing a mathematical model, button opak, jumbo opak, and huge round opak were thought to be distinct kinds of opak. The findings of the study indicate that 37,000 kg of cassava as the primary raw material, UD Opak Rizky must manufacture 3,125 kg of button opak, 0 kg of jumbo opak, and 0 kg of huge round opak daily. The goal is to maximize the profit function Z while adhering to four limitations for limited raw resources. The profit obtained by UD Opak Rizky from 37,000 kg of cassava with this production amount was IDR 10.581.880,00.